Characteristics Analysis of PM2.5 in Industrial Complex Near Area According to Domestic and Foreign Influences in Case of High Concentration PM2.5 Episode Occurrence 고농도 PM2.5 발생 시 국내외 영향에 따른 산업단지 인근 지역의 PM2.5 특성 분석 - Kim, Chang Hyeok; Kim, Jeongho; Hwang, Kyucheol; Kim, Pilho; Shin, Su Hyun; Park, Jong Sung; Park, Sechan; Lee, Gahye; Lee, Jae Young; Kim, Jong Bum (Journal of Korean Society for Atmospheric Environment, 2023)
It is very important to investigate domestic and foreign influence of PM2.5 in case of high concentration PM2.5 episode occurrence. In this study, the mass concentrations and chemical compositions of PM2.5 were measured in the Sihwa National Industrial Complex at one-hour intervals between January 1 and December 31 2021, to determine characteristics of PM2.5 High-level PM2.5 were identified and the characteristics of their corresponding periods were analyzed. The prevailing wind direction throughout the study period was northwesterly with a relatively high frequency of no wind (41%). NO3 - (26.9%) was the highest component of PM2.5, followed by NH4 + (13.0%), OC (12.9%), and SO4 2- (12.5%). Periods with a daily average concentration 75 μg/m3 or more were classified as high PM2.5 concentration cases. Five cases were identified as high concentration during the study period. The causes of these cases were presumed to originate from domestic sources for case 1 and 2, from abroad for case 3 and 4, and from a mixture of both domestic and abroad for case 5. In the cases with domestic sources, NO3 - and NH4 + were high contributors and in the cases with foreign sources. And, Metal was high contributors. These findings can be helpful to understand high PM2.5 events and can be used to establish air quality improvement policies.
Keywords: Domestic; Foreign; High PM2.5 episode; Industrial complex; Influence; PM2.5